Job embeddedness model and employee intention to stay in ICT industries of Malaysia - Ayesha, Noor; Yuserrie, Zainuddin (2016)
The retention of IT professionals is a main problem in information and communication industry (ICT) in Malaysia. This is because the influence of environment factors such as business growth, imbalance between demand and supply and high turnover rate among information technology (IT) employees have made retaining them becoming more crucial. This work represents a framework that identifies necessary factors for IT professionals in their current organizations. The framework is based on the Job Embeddedness Model introduced by Mitchell and his co-authors. It takes into consideration the organizational fit of IT professionals, the ICT industries are not only part of leading organizations, but their organizational fit are also significantly related to retain their employees. Such an organizational fit atmosphere introduces additional challenges along the dimensions of temporal, cultural, organizational, geographical, functional, and business and technological knowledge that may eventually affect the decision of whether to stay with or to leave current organization. Skilled and talented IT professionals are assets to organizations. When they leave, loses in the forms of human, knowledge, and social capital can be so substantial that it affects the operations of employees and organization. Therefore, an important agenda for an industry to understand the factors that will attract employees to stay with their current organizations so that effective retention programs can be formulated to keep the best IT employees productively engaged for a long-term.